PEREMPUAN DALAM PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - Wakhidah, M.Si, Nur (EGALITA, 2006)
The development of science and technology influence all aspects of life. The development is not only dominated by men but also by women. Women are considered as the user of the invention of science and technology  while men  are the inventor. Men, explicitely, pose role in the process of science and technology. However, scienctists propose findings that show  women's identity of technology. It is predicted by those who are concerned with women issues that there will be more women involving in the process of inventions in science and technology. This achievement  of women is inevitable as they have contributed much on the development of  that area whether it is publicly accepted or not.